2016
DOI: 10.1136/annrheumdis-2016-eular.3130
|View full text |Cite
|
Sign up to set email alerts
|

AB0030 Cytokine Profiles in Systemic Lupus Erythematosus and Rheumatoid Arthritis

Abstract: BackgroundOur aim was to compare serum levels of cytokines in patients with systemic lupus erythematosus (SLE) and rheumatoid arthritis (RA).ObjectivesComparative data on cytokine profile in SLE and rheumatoid arthritis RA patients are scarce.MethodsWe examined serum samples from 80 pts with SLE, median and interquartile range (25th–75th percentile) of disease duration 48 (2–432) months; age 31,5 (16–65) years; 72 female; 74 pts with RA, disease duration 90,0 (30,00–192,0) months; age 54,0 (44,0–62,0) years; 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…Eotaxin and MIP-1α levels were not significantly different between groups. However, a study by Novikov et al showed that the expression of otaxin and MIP-1α was significantly lower in patients with SLE than in those with rheumatoid arthritis (RA) group [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Eotaxin and MIP-1α levels were not significantly different between groups. However, a study by Novikov et al showed that the expression of otaxin and MIP-1α was significantly lower in patients with SLE than in those with rheumatoid arthritis (RA) group [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among 241 eligible studies meeting the inclusion criteria, 76 articles were excluded due to unextractable data, insufficient data on HCs, irrelevant VEGF sample type (urine/synovial fluid/tear fluid), or inappropriate disease control groups. Finally, 165 studies were included in the meta-analysis, with 28, 29, 40, 13, 8, 12, 16, 23, and six studies on SLE ( 20 , 21 , 26 51 ), RA ( 12 , 22 24 , 38 , 43 , 52 74 ), SSc ( 11 , 38 , 39 , 64 , 75 110 ), BD ( 111 – 123 ), KD ( 18 , 124 – 130 ), AS ( 55 , 73 , 131 – 140 ), IBD ( 141 156 ), PsA ( 12 , 14 , 135 , 136 , 157 175 ) and GD ( 10 , 176 180 ), respectively. The main study characteristics are summarized in Table 1 and Appendix 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, chemokines, a category of chemoattractant cytokines, contribute significantly to the pathogenesis of SLE and its complications, notably lupus nephritis ( 58 ). The research by Novikov A, et al., indicates a notably lower expression of Eotaxin in the SLE group compared to those with rheumatoid arthritis ( 59 ), highlighting the unique inflammatory profiles in these conditions. IL-22RA1, an essential component of the IL-22 receptor complex, has been observed to decrease in serum and plasma levels as reported by Cheng and Pan ( 60 , 61 ).…”
Section: Discussionmentioning
confidence: 99%